2019
DOI: 10.1007/s12369-019-00526-x
|View full text |Cite
|
Sign up to set email alerts
|

Robot Acceptance at Work: A Multilevel Analysis Based on 27 EU Countries

Abstract: Robots are increasingly being used to assist with various tasks ranging from industrial manufacturing to welfare services. This study analysed how robot acceptance at work (RAW) varies between individual and national attributes in EU 27. Eurobarometer surveys collected in 2012 (n = 26,751) and 2014 (n = 27,801) were used as data. Background factors also included country-specific data drawn from the World Bank DataBank. The study is guided by the technology acceptance model and change readiness perspective expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Next to design variations (e.g., zoomorphic, caricatured [21]), the context should continue to be considered in a broader sense. On the one hand, this refers to the integration of further automation contexts (e.g., smart living environments [48]) and, on the other, to the investigation of cultural and country-specific differences as the acceptance of robot technology and trust may be motivated both personally and socially [22,49]. Since the participants of this survey were acquired in Germany, it would be of great interest to examine the extent to which the obtained key findings are different or similar as regards the perception and evaluation of test persons with diverse cultural backgrounds, experience in dealing with, and attitudes toward robots, especially as there are already indications for cultural differences in users' likability and trust toward robots between Germany and Asian cultures, for example [22].…”
Section: Limitationsmentioning
confidence: 99%
“…Next to design variations (e.g., zoomorphic, caricatured [21]), the context should continue to be considered in a broader sense. On the one hand, this refers to the integration of further automation contexts (e.g., smart living environments [48]) and, on the other, to the investigation of cultural and country-specific differences as the acceptance of robot technology and trust may be motivated both personally and socially [22,49]. Since the participants of this survey were acquired in Germany, it would be of great interest to examine the extent to which the obtained key findings are different or similar as regards the perception and evaluation of test persons with diverse cultural backgrounds, experience in dealing with, and attitudes toward robots, especially as there are already indications for cultural differences in users' likability and trust toward robots between Germany and Asian cultures, for example [22].…”
Section: Limitationsmentioning
confidence: 99%
“…Aligning the cobot's position to the employee's body dimensions was considered average important (M = 3.57). The same holds true for employee demographics (M = 3.23) like age, gender, and cultural background, although prior research reveals that individual as well as cultural factors shape the acceptance of cobots, since they are often related to the affinity for technology [112].…”
Section: Appropriate Cobot Configurationmentioning
confidence: 88%
“…Therefore, these empirical results cannot be generalized to other countries, especially since previous studies highlight the influence of a subject's culture on their general attitude toward robots and their willingness to work with them [116]. However, cross-natural studies revealed that individual factors are usually more important than country-specific ones when it comes to robot acceptance at work, which suggests that results should be transferrable to other countries at least to some extent [112]. Thereby, it has to be taken into account that the density of industrial robots in Germany is far above average with 338 units per 10,000 employees compared to 99 units per 10,000 employees worldwide [1].…”
Section: Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…The use of robots may increase and improve the quality of products as well as decrease production costs. Nowadays, robots are widely used as workers in manufacturing sectors to replace human workers [28], [29]. Examples of manufacturing robots' tasks include packaging, locating, assembling, and so on [30].…”
Section: Roboticsmentioning
confidence: 99%